Will Knjaz Miloš Belong to Foreigners? The Privatization and Image of Multinational Companies in the Serbian Media (2000-2005) - Vladimir Miokov (University of Belgrade, 2016)
This study analyses the media coverage of the privatization of Knjaz Miloš, Serbia’s most famous mineral water factory, as well as the manner in which the multinational companies were presented in this process. The focus of the paper is on the conflict between major stakeholders as they were presented in analyzed media texts. Three phases of the privatization process are analysed in this paper. The first phase is the period from October 2000 to September 2003, when the news about privatization came out in the media; the second phase is from August 2003 to December 2003, when the first potential buyers appeared; and third is the period from August 2004 to September 2005, when Knjaz Miloš was finally privatized. The conclusion of this analysis is that a negative image of multinational companies prevails in the domestic media. Such an image is not ideologically coloured (as it was in the 1990s) and is seldom openly presented. The general attitude is sceptical, even though an awareness of the importance of the participation of multinational companies in the process of privatization is present.